The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/26410397.2020.1832291
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent sexual and reproductive health and universal health coverage: a comparative policy and legal analysis of Ethiopia, Malawi and Zambia

Abstract: Universal Health Coverage (UHC) forces governments to consider not only how services will be provided – but which services – and to whom, when, where, how and at what cost. This paper considers the implications for achieving UHC through the lens of abortion-related care for adolescents. Our comparative study design includes three countries purposively selected to represent varying levels of restriction on access to abortion: Ethiopia (abortion is legal and services implemented); Zambia (legal, complex services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…There are lapses in the current SRH policy framework [ 29 , 48 ], which make it difficult for deaf persons to access necessary information. Thus, there is a need for health policymakers to design robust policies tailored to suit the uniqueness of deaf persons.…”
Section: Conclusion and Study Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are lapses in the current SRH policy framework [ 29 , 48 ], which make it difficult for deaf persons to access necessary information. Thus, there is a need for health policymakers to design robust policies tailored to suit the uniqueness of deaf persons.…”
Section: Conclusion and Study Implicationsmentioning
confidence: 99%
“…There is a corpus of literature on challenges relating to the accessibility of SRH services, especially in sub-Saharan African contexts [ 13 , 16 , 24 – 27 ]. Most studies have reported that challenges such as lack of policies [ 28 , 29 ], low education levels [ 30 ], poverty [ 12 , 24 , 31 , 32 ], culture [ 33 , 34 ], stigma [ 8 , 16 ] and lack of parental support [ 14 , 35 ] contribute to the inability of girls and women to access SRH services. Other studies have also found that a high prevalence of teenage pregnancy is likely linked to factors such as poverty [ 12 , 25 ], illiteracy [ 30 , 36 – 38 ] and lack of awareness of contraceptive methods [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…65 In Malawi, the current colonial-origin law precludes adolescents from accessing a safe procedure, (re-)enacting structural violence through a denial of services and the lack of recognition of adolescents' specific abortion needs. 66 Restrictive abortion laws are experienced as direct forms of violence, but all abortion laws-even more liberal ones-enact barriers to full reproductive freedom. 67 These laws overlap with and are enacted alongside other punitive laws-criminalization of HIV nondisclosure, 68 "defilement laws" 69 or mandatory reporting requirements 70 -that create and legitimize conditions of violence and inequity.…”
Section: •Structural Violence In National and Transnational Policiesmentioning
confidence: 99%
“…In some cases, girls in Malawi may be unable to seek antenatal care because of laws that require the presence of a partner at visits [22]. In contrast, Zambia has better access to sexual and reproductive health services, particularly with access to safe abortion, relative to Malawi [23]. Local laws and policies should focus on identifying those among AGYW who become pregnant before marriage and are at highest risk of insufficient antenatal care in Malawi and make antenatal care more accessible to them, given that the use of maternal health care services is associated with other maternal and child health outcomes [24,25].…”
Section: Discussionmentioning
confidence: 99%